2016
DOI: 10.1038/srep38015
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori is associated with dyslipidemia but not with other risk factors of cardiovascular disease

Abstract: Epidemiologic and clinical data suggest that Helicobacter pylori infection is a contributing factor in the progression of atherosclerosis. However, the specific cardiovascular disease risk factors associated with H. pylori remain unclear. We performed a cross-sectional study of 37,263 consecutive healthy subjects who underwent a routine health check-up. In multivariable log Poisson regression models adjusted for potential confounders, the associations of H. pylori seropositivity with higher LDL-C (relative ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
64
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 38 publications
7
64
0
3
Order By: Relevance
“…The association of H. pylori infection with lipid profile changes was observed earlier in 1996 in Finnish subjects, their serum cholesterol and TG levels were significantly higher in H. pylori-infected male persons after adjustment of age and BMI (Buzas et al 2014). More recently, Kim et al (2016) have found that subjects with H. pylori infection had higher total cholesterol and LDL-C, as well as lower HDL-C. They explained that alterations of lipid profile may be mediated by inflammatory cytokines such as IL-1, IL-6, or tumor necrosis factor-α (TNF-α) through a chronic inflammatory condition induce by H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…The association of H. pylori infection with lipid profile changes was observed earlier in 1996 in Finnish subjects, their serum cholesterol and TG levels were significantly higher in H. pylori-infected male persons after adjustment of age and BMI (Buzas et al 2014). More recently, Kim et al (2016) have found that subjects with H. pylori infection had higher total cholesterol and LDL-C, as well as lower HDL-C. They explained that alterations of lipid profile may be mediated by inflammatory cytokines such as IL-1, IL-6, or tumor necrosis factor-α (TNF-α) through a chronic inflammatory condition induce by H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…Following the aforementioned initial reports, there have been amounting data from observational studies (mostly cross‐sectional) having evaluated the potential association between H pylori ‐I and NAFLD . The main characteristics and results of these studies are summarized in Table .…”
Section: Clinical Studies On the Association Between Helicobacter Pylmentioning
confidence: 99%
“…Following the aforementioned initial reports, there have been amounting data from observational studies (mostly cross-sectional) having evaluated the potential association between H pylori-I and NAFLD. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] The main characteristics and results of these studies are summarized in Table 1. The majority of them (n = 12) have been carried out in Asia (China, South Korea, Japan, and Turkey), two in Europe (Greece and Spain), and one in the USA.…”
mentioning
confidence: 99%
“…However, the multivariable analysis-adjusted potential confounding factors showed that H. pylori infection was not associated with fasting blood glucose or HbA1c. 3 The association between H. pylori infection and diabetes mellitus and glucose intolerance remains controversial. A meta-analysis of 41 studies revealed a higher prevalence rate of H. pylori in diabetic patients than in nondiabetic patients.…”
Section: Age and Gender May Be The Key Points In Hyperglycemic Patienmentioning
confidence: 99%
“…Recently, we investigated the association between H. pylori infection and each component of metabolic syndrome. 3 The study included 37 263 asymptomatic men and women undergoing a routine health check-up and found that the levels of fasting blood glucose and glycated hemoglobin (HbA1c) were significantly higher in participants with H. pylori infection. Also, diabetes mellitus was more prevalent in individuals with H. pylori.…”
mentioning
confidence: 99%